AN EXPLORATORY VIEW OF THE FOUNDATIONS OF FOREIGN TRADE ENTREPRENEURSHIP (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
This study aims to reveal the foreign trade entrepreneurship and entrepreneurial tendency in the context of economic nationalism which expresses a protective approach in terms of foreign trade policy which is one of the main components of the policy of economics. The study was designed as a single case study from qualitative research designs. The sample of the study consists of foreign trade entrepreneurs who have been in foreign trade for at least five years and who are in the industry as a producer/manufacturer. In the study, the semi-structured interview technique was used for the data gathering process. A purposeful sampling technique was used in order to determine enterprises and individuals to conduct interviews. The findings of the data analysis showed that the foreign trade policy adopted by the individual is the basis of the commercial activity. The result of the study was examined in two dimensions as “foreign trade entrepreneurship” and “international entrepreneurship”. It shows that the companies are predominantly foreign trade entrepreneurs in the context of evaluating the income obtained from abroad, benefiting from incentives, future targets, opportunities and threats of foreign commercial activities. For this reason, the finding obtained reveals that the firms subject to the study are mainly economically nationalist. Considering the this, it is suggested to support foreign trade entrepreneurs, who act mainly with an economically nationalist motivation, to find new market opportunities abroad, to increase the government incentives for bringing the foreign currency revenues to the country and to facilitate the access of companies to them.